Kinetic Study On The Thermal Degradation Of Polyvinylpyrrolidone (Pvp) - El Ghemi, Abduel Hamid N (2003)
Thermogravimetric analysis (TGA) data (thermogravimetric curves TG and derivative thermogravimetric curves DTG) were used to provide an alternative model of the kinetics of plastics waste degradation to the current model based on molecular weight distribution (MWD) measurement. TGA models traditionally consist of assumed 'pseudo first order' kinetic equations. The thermal degradation kinetics of polyvinylpyrrolidone (PVP) was investigated by dynamic thermogravimetry, in a nitrogen atmosphere, over the temperature range 25-800 °c and at constant nominal heating rates of 5 , 1 0, 20, and 30 °C/min, respectively. Two distinct mass change stages in the thermogravimetric analysis (TGA) curves indicated that the degradation of polyvinylpyrrolidone (PVP) might be attributed to two reactions. The method developed to accommodate this kinetic study involved treating the data as a pseudo first-order reaction. The corresponding activation energies, frequency factors and reaction orders of the two reactions were determined. The TG thermgrams (TGA curves and DTG curves) obtained from TGA showed the same shape and trend at different heating rates of 5, 1 0, 20, and 30°C/min. To accommodate this mechanism change, the data were treated as pseudo first-order reaction. A single first-order fit provided a good correlation of the data obtained at different heating rate for polyvinylpyrrolidone (PVP). A simple relationship was developed to predict the activation energy for the pyrolysis process. The activation energy was found to be in good agreement with past experimental using polyvinylpyrrolidone (PVP).